Lactate-Mediated Signaling in the Brain—An Update - Barbara Vaccari-Cardoso; Maria Antipina; Anja G. Teschemacher; Sergey Kasparov (Brain Sciences, 2022)
Lactate is a universal metabolite produced and released by all cells in the body. Traditionally it was viewed as energy currency that is generated from pyruvate at the end of the glycolytic pathway and sent into the extracellular space for other cells to take up and consume. In the brain, such a mechanism was postulated to operate between astrocytes and neurons many years ago. Later, the discovery of lactate receptors opened yet another chapter in the quest to understand lactate actions. Other ideas, such as modulation of NMDA receptors were also proposed. Up to this day, we still do not have a consensus view on the relevance of any of these mechanisms to brain functions or their contribution to human or animal physiology. While the field develops new ideas, in this brief review we analyze some recently published studies in order to focus on some unresolved controversies and highlight the limitations that need to be addressed in future work. Clearly, only by using similar and overlapping methods, cross-referencing experiments, and perhaps collaborative efforts, we can finally understand what the role of lactate in the brain is and why this ubiquitous molecule is so important.